Off-label drugs use in pediatric palliative care. - De Zen, Lucia; Marchetti, Federico; Barbi, Egidio; Benini, Franca (Ital J Pediatr, 2018)
BACKGROUND: Paediatric palliative care (PPC) aim to ensure the control of symptoms and the best possible quality of life for patients whose underlying disease, characterized by an unstoppable evolution and negative prognosis, no longer responds to specific treatments. The scientific evidence in this context are very deficient and, in order to obtain welfare objectives consistent with the situation, in the overwhelming majority of cases the prescription of drugs is off-label for indication of use and/or for age and/or for way of administration and/or formulation. The Agenzia Italiana del Farmaco - AIFA and the Italian Society of Palliative Care (Società Italiana di Cure Palliative - SICP), under a dedicated working group, wrote a document that collects the scientific evidence available to support the off-label use of medicines more frequently used in PPC. The goal is to certify the consolidated off-label use of these drugs and propose their use under the Law 648/96, in the absence of data from its pivotal clinical trials. Aim of the commentary is to report the conditions for this important work and to present the 10 drugs, usually used off-label in PPC and in pain therapy, now included in Law 648/96. CONCLUSION: This work is deemed essential to resolve, at least in part, the lack of availability of medicines researched and approved.